CLASSIFICATION OF SOCIO-CULTURAL PROCESSES OF PROFESSION AND ITS SURROUNDING AREAS IN ANCIENT AND EARLY MIDDLE AGES (Conferencea, 2024)
The ancient and medieval Kasbi and its surroundings are unique. At the same time, in addition to the fact that they are a common cultural space, some of its regions, especially Kasbi and the adjacent territories, have their own relatively separate development and cultural features. This article expresses opinions about the historical, cultural, political realities, historical roots, foundations and factors of these processes that took place in Kasbi and its surrounding areas.